A STUDY ON RELATIONSHIPS AMONG AGE, BODY WEIGHT, ORCHIDOMETRY AND SEMEN QUALITY PARAMETERS IN ADULT CHOLISTANI BREEDING BULLS - S. A. Mahmood; Ijaz; A. N. Ahmad; H. Rehman; H. Zaneb; U. Farooq (Journal of Animal and Plant Sciences, 2014)
The present study was designed to 1) assess preliminary non-invasive, readily measurable reproductive attributes of Cholistani breeding bulls (n=06) such as age, body weight (BW) and orchidometric parameters viz. scrotal circumference (SC), scrotal skin fold thickness (SSFT), average testicular length (Avg L), average testicular width (Avg W), and paired testicular volume (PTV); 2) assess the baseline semen attributes such as volume (mL), mass motility (Score 1-5), individual motility (%), sperm concentration (million/mL), viability (%), morphology (%) and acrosome integrity (%); and 3) determine relationship among dependent and independent variables mentioned in objectives 1 and 2.. The overall means for age, BW, SC, SSFT, Avg L, Avg W, and PTV for these bulls were 92.83±28.15 months, 520.±42.31 kg, 36.02±2.25 cm, 1.10±0.15cm, 16.91±0.70 cm, 7.05±0.35 cm, and 874.37±137.07 cm3, respectively. Similarly, the overall means for semen volume, mass motility, individual motility, sperm concentration, viability, normal morphology and acrosome integrity were 4.46±1.65mL, 1.95±0.25, 63.46±4.91%, 903.22±182.04 million/mL, 85.35±2.29%, 85.66±2.51% and 84.74±2.62%, respectively. The results of correlation analysis amongst the independent variables revealed positive correlations between BW:Avg L (r=0.920), SC: Avg W (r=0.922) and SC:PTV (r=0.957) at P<0.01; and between BW:PTV (r=0.856) and Avg W:PTV (r=0.851) at P<0.05. The inter relationship between independent and dependent variables showed maximum correlation of age with other semen attributes. The results of this study demonstrate that the reproductive indices of Cholistani breeding bulls are at par with those of Sahiwal bulls. Furthermore, the orchidometric measurements along with age and body weight remain reliable and readily measurable indicators of reproductive potential of breeding bulls.
Keywords: Cholistani bulls; age; body weight; orchidometry